Phase formation and surface morphology of nickel doped Ba1−xSrxTiO3 ceramics prepared by sol–gel technique - Kakumani, Asa Deepthi; Ruthramurthy, Balachandran; Ong, Boon Hoong; Wong, Hin Yong; Tan, Kar Ban; Yow, Ho Kwang; Daud, Z. B. M. (Maney Publishing, 2014)
Varied compositions in the barium strontium titanate ternary system were prepared through the slow injection sol–gel technique. Nickel dopant was introduced through a general formula of Ba1 −xSrxTi1 −yNiyO3 (x = 0·4 and 0·5; y = 0·1 and 0·4 mol-%). Thermogravimetric analysis revealed that barium strontium titanate gels were completely dried and stabilised at 1000°C. All barium strontium titanate samples were confirmed as phase pure perovskite by qualitative X-ray diffraction analysis in which Nickel-doped subsolidus solution was formed successfully after calcinations at 1000°C. On the other hand, there was a sign of agglomeration discernible in the prepared BST samples and the grain sizes were found to be in the range of 39·66–71·87 nm.